Improving Elementary School Students' Science Literacy through Office Sway Interactive Learning Media - Sulastri, Dewi; Andriana, Encep; Syachruroji, A (EDUCARE: Journal of Primary Education, 2024)
This study addresses the need to improve science literacy among elementary school students. Although traditional teaching methods are important, they sometimes fail to fully engage students or deepen their understanding of the material. Therefore, this study explores the potential of using Office Sway as an interactive learning media to enhance science literacy. The aim of this study is to assess the effectiveness of using Office Sway in supporting the improvement of science literacy among elementary school students. This study also seeks to understand how Office Sway can enhance student engagement and deepen their understanding of scientific concepts through interactive multimedia elements. The results of the study show that Office Sway has significant potential to increase student engagement and science literacy in elementary schools by presenting content in a more dynamic and engaging way through interactive multimedia features. However, the success of using Office Sway heavily depends on several factors, such as well-structured teacher training, supportive technological infrastructure, and continuous content updates. To maximize its effectiveness in learning, a holistic approach and continuous evaluation are necessary. This study provides important contributions by identifying the potential of Office Sway as a learning tool that can enhance student engagement and understanding of scientific concepts, while also highlighting the importance of teacher training, proper infrastructure, and ongoing evaluation.